MS-Computer Science Feedback 2017 (2017)
MS in Computer Science: MS has been re-worked over the last 2 years and has focused on student scholarships. Committee agrees with need for faculty to continue to consider distinguishing outcomes between degrees to ensure that outcome levels appropriate for graduate degree. Need to include a clear assessment plan in the MOU/Action plan. Committee encourage program to put plans to establish an advisory board and strengthening internship opportunities into their MOU/Action Plan Internships for students.